Một số vấn đề cơ bản của việc hoàn thiện mô hình trường Phổ thông Dân tộc Nội trú(PTDTNT) - Phạm, Vũ Kích (Bộ Giáo dục và Đào tạo, 2013)
In this paper, the author deals with some actual situations of special schools for minirity pupils and orientation of it's development in coming years.